Trait‐level and momentary correlates of bulimia nervosa with a history of anorexia nervosa. Issue 2 (18th September 2012) - Goldschmidt, Andrea B.; Peterson, Carol B.; Wonderlich, Stephen A.; Crosby, Ross D.; Engel, Scott G.; Mitchell, James E.; Crow, Scott J.; Cao, Li; Berg, Kelly C.
Abstract Objective: Some investigators have suggested subtyping bulimia nervosa (BN) by anorexia nervosa (AN) history. We examined trait‐level and momentary eating‐related and psychosocial factors in BN with and without an AN history. Method: Interview, questionnaire, and ecological momentary assessment data of eating‐related and psychological symptoms were collected from 122 women with BN, including 43 with (BN+) and 79 without an AN history (BN−). Results: Body mass index (kg/m2) was lower in BN+ than BN− (p = 0.001). Groups did not differ on trait‐level anxiety, shape/weight concerns, psychiatric comorbidity, or dietary restraint; or on momentary anxiety, dietary restriction, binge eating, purging, or exercise frequency, or affective patterns surrounding binge/purge behaviors. Negative affect increased prior to exercise and decreased thereafter in BN+ but not BN−, although groups did not statistically differ. Discussion: Results do not support formally subtyping BN by AN history. Exercise in BN+ may modulate negative affect, which could have important treatment implications. © 2012 by Wiley Periodicals, Inc. (Int J Eat Disord 2013)